EDUCATION AS A MEDIUM FOR LANGUAGE PRESERVATION: AN ETHNOGRAPHIC STUDY ON THE LIMOLA LANGUAGE IN SASSA VILLAGE - Hakim, M. Nur; Hidayat, Wahyu; Jusrianto, Jusrianto (Universitas Labuhanbatu, 2025)
Purpose – This study examines the role of education as a medium for preserving language and identity, with a focus on the Limola language in Sassa Village, South Sulawesi.Methodology – To investigate this, the research employed a qualitative ethnographic approach. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, parents, local leaders, and the community.Findings – The findings reveal that Limola use in formal education remains limited. It is currently included only in the subject of Regional History and Culture, lacking curricular support, textbooks, or official guidelines. Nevertheless, students show a positive attitude and strong enthusiasm toward learning Limola vocabulary, suggesting potential for revitalization through education. Meanwhile, parents tend to use Indonesian at home to support academic achievement. Local leaders, on the other hand, emphasize the importance of maintaining Limola as a marker of cultural identity.Contribution – The study concludes that education offers an opportunity to revitalize the Limola language with a culture-based approach and innovative technologies. However, to succeed, this effort needs inclusive policy support, teacher training, new teaching materials, and collaboration between schools, the government, and local communities.